Narrative Analysis of Gender Construction in Modern English Literature - Iin Almeina Loebis (Pusdikra-Publishing.com, 2026)
This research examines the construction of gender in modern English literature through a narrative analysis of the representation and negotiation of gender identity in contemporary socio-cultural contexts. The approach used is a qualitative analysis with a focus on works of modern English literature published in the late 20th to early 21st centuries. The theoretical frameworks used include feminist theory and narrative theory to examine how gender is formed through characterizations, storylines, points of view, and symbolic structures in texts. The results suggest that modern English literature tends to represent gender as a dynamic social construct and is no longer seen as a fixed biological identity. The authors utilize a variety of narrative strategies, such as fragmented plots, unreliable narrators, and perspective shifts, to deconstruct traditional gender norms as well as display the complexities of identity formation. In addition, dominant themes such as resistance to patriarchal structures, the redefinition of masculinity and femininity, and the emergence of non-binary gender representation were found. This research also confirms that narrative techniques have an important role in shaping readers' understanding of gender issues. Thus, narrative analysis makes a significant contribution to understanding the dynamics of gender construction in modern English literature as well as the development of gender discourse in contemporary contexts.